CONCRETE STRUCTURES FOR HIGH RELIABILITY OF SPECIAL PURPOSE - , М. В. (Municipal economy of cities. Series: «Economy science», 2013)
<span title="Предложен способ повышения долговечности бетонных и железобетонных конструкций специального назначения за счет модифицирования состава бетонной смеси для обеспечения полифункциональности процесса структурообразования бетона.">We propose a method of increasing the durability of concrete and reinforced concrete structures for special purposes at the expense of modifying the composition of the concrete mix to provide multi-functionality of the process of structure of concrete. <span title="Решение задачи ориентировано на разработку научных основ технологических и конструктивных мероприятий, обеспечивающих безотказную работу конструкций при минимальных затратах времени и средств на техническую эксплуатацию и ремонт зданий, а также снижение материальных потерь от простоев в период ремонтов при регламентированном сроке службы зданий и сооружений.">Solution of the problem is focused on the development of scientific bases of technological and design measures to ensure trouble-free operation of structures with minimal time and money on maintenance and repair of buildings, as well as the reduction of material losses from operational downtime during repairs at a regulated service life of buildings and structures.